Fast Track Initiative : Building a Global Compact for Education - World Bank (Washington, DC, 2012)
The Education for All -- Fast Track Initiative (FTI) was launched in 2002 as a partnership between donor and developing countries to accelerate progress towards the Millennium Development Goal (MDG) of universal primary education. FTI is built on mutual commitments: 1) partner countries have agreed to give priority to primary education and to develop sound national education plans, and 2) donors have agreed to increase support in a transparent, coordinated manner. This paper includes the following headings: the Education for All -- Fast Track Initiative (FTI); FTI promotes education policy reform; FTI promotes aid effectiveness; monitoring and evaluation; FTI trust funds; and expansion of FTI.